Intercultural Interpretation in the Inter-American Court of Human Rights - Brevis Cartes, Priscilla (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper sentences from the Inter-American Court of Human Rights are analysed in search of an intercultural interpretation that could address the criticism regarding human rights’ ethnocentrism. The study’s approach is hermeneutic philosophy and its methodology is qualitative research, with the use of document analysis. As a conclusion, an intercultural interpretation and an interpretive dialogue between human rights texts and the worldview of indigenous cultures were found, even though a further development is needed to determine a general criterion of interculturality.